2022
DOI: 10.1055/s-0042-1742769
|View full text |Cite
|
Sign up to set email alerts
|

Children with Conductive Hearing Loss Fitted with Hearing Aids: Outcomes and Caregiver Experiences in South Africa

Abstract: Introduction Hearing aids are a frequent management option for children with conductive hearing loss (CHL) and it is necessary to determine the efficacy of outcomes. Limited information regarding caregivers' perceptions and experiences are available to examine outcomes in this population. Objectives To describe hearing aid outcomes and caregivers' experiences for children with CHL who wear behind-the-ear (BTE) hearing aids. Methods Retrospective review of clinical data from 19 children betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Hearing technology is only effective if consistently used (Gan et al, 2017 ). Average data logging was 7.0 h/day for the sample in this study, which is higher than reported device use with air-conduction hearing aids in three previous South African studies (Booysen et al, 2021 ; Kuschke et al, 2021 ; Van Zyl et al, 2022 ), but still falls short of the daily recommended average device use of 10 h/day for optimal speech- and language development through audition (Tomblin et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Hearing technology is only effective if consistently used (Gan et al, 2017 ). Average data logging was 7.0 h/day for the sample in this study, which is higher than reported device use with air-conduction hearing aids in three previous South African studies (Booysen et al, 2021 ; Kuschke et al, 2021 ; Van Zyl et al, 2022 ), but still falls short of the daily recommended average device use of 10 h/day for optimal speech- and language development through audition (Tomblin et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 50%
“…Continued research into paediatric hearing loss and outcome measures in audiological practice is essential to profession growth and person-centred care. Recently, three studies in South Africa looked at the outcomes of children with hearing loss; however, all focused on children fitted with behind-the-ear hearing aids (Booysen et al, 2021 ; Kuschke et al, 2021 ; Van Zyl et al, 2022 ). In low-resourced contexts, where middle ear pathologies and various syndromes associated with hearing loss are common (Kesser et al, 2013 ), data on the context-specific functional hearing outcomes for children who wear BCHD is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The umbrella term for the child with special needs encompasses visually impaired, deaf, mentally retarded, physically disabled, hearing impaired, learning difficulties, behavioral disorders, gifted, and healthimpaired children, each requiring tailored educational services [12]. Deaf children experience hearing loss due to malfunctioning hearing aids, necessitating specialized guidance and education for language and skill development [13]. Their language acquisition differs from that of typically developing children, relying on full communication, which utilizes various forms such as sign language, reading, writing, and speaking [14].…”
Section: Introductionmentioning
confidence: 99%